Internal and External Factors Influencing Waste Sorting Practices: A Behavioral Study at Higher Education - Dinda Sandikta Putri; Muhammad Khairunnazmi; Muhammad Artdiaz Agvito Latif; Abdullah Ramadhan; Muhammad Ariq Fauzi (Telkom University, 2025)
This study examines both internal and external factors that affect students' waste sorting behavior at Telkom University, an academic institution that struggles with sorting compliance even after establishing